ARTICLE REVIEW: POTENTIAL PHARMACOLOGICAL ACTIVITY OF LOBI-LOBI FRUIT (Flacourtia inermis, Roxb) - Adiwinata, Much Cheril Wicaksono; Vitamia, Cszahreyloren (Universitas Muhammadiyah Ahmad Dahlan Cirebon, 2025)
The Lobi-lobi fruit is a tropical plant that is rich in secondary metabolites. Many studies have discussed the usefulness of secondary metabolites in this fruit. This study aimed to explore the secondary metabolites and pharmacological activities of lobi-lobi fruit (Flacourtia inermis, Roxb). The methods used included a literature review of various scientific journals discussing the health potential of fruits. The results showed that the lobi-lobi fruit extract had significant antioxidant activity with an IC50 value of 104.223 ?g/mL, and showed potential as an antidiabetic and antibacterial agent. This discussion highlights the importance of bioactive components, such as phenolics, for providing therapeutic effects. The conclusion shows that this fruit has potential as a source of natural medicine and requires further research. Keywords: secondary metabolites, flacourtia inermis, pharmacological activity